Avaliação do fluxo da atenção às cirurgias pediátricas no oeste do Paraná - Talini, Carolina (2023)
Pediatric surgery receives great demand for referrals from primary care services, in order, to evaluate the need for surgical intervention. However, access to this specialized evaluation and intervention does not always occur at the appropriate time. This study aims to characterize the profile of pediatric patients electively operated in western Paraná state region, between 2018 and 2020. This is a qualitative and quantitative, descriptive, cross-sectional and retrospective study, consisting of two stages: the first, quantitative, sought to outline the profile of children referred for surgery and identify those late referred by reviewing electronic medical records of three different SUS outpatient clinics that belong to the 10th Parana State health region. The second stage, qualitative, interviews were carried out by telephone calls, from March to May 2022, with the responsible for patients who were identified as being late under surgery. Evaluated data were epidemiologic data, information on underlying diseases, referral data, specialist assessment and surgical procedure. In the interview, the reasons that led to the delay in the diagnosis, referral and performance of the patient's surgical procedure were specifically questioned, the path taken by the parents from the diagnosis to the resolution of the problem. During this period, 410 patients underwent an elective surgical procedure, of which 289 were included in the research. The sample was predominantly male (72.3%), originated from Cascavel (52,6%), with a mean age of 57.9 months at the surgeon's assessment and 59 months at the date of surgery. Most of the patients came from primary care (75%) and the most common pathology was inguinal hernia (39.1%). The mean time interval between referral through primary care and surgery was 4.98 months, and between the surgeon's assessment and surgery was 1.21 months. Of the total sample, 77 (26.6%) patients were identified as being referred late for the surgical procedure. Regarding the qualitative approach, parents demonstrated varied perspectives related to the time perception between the diagnose, referral, surgical evaluation, and the surgical procedure. Three categories emerged: difficulties encountered; care in primary care and from discovering the problem to performing surgery. Regarding the wait for the expert assessment, there is an excess of demand against a lower availability of appointments. A positive aspect was the quality of care received in primary care. Scarcity of specialists and lack of coordination in primary care network can be raised as contributing factors to the difficulties encountered in this process between referral and surgery. Family members interviewed recognized the wait as satisfactory and as expected. Despite initial difficulties, all had their surgeries performed and considered the care received as quality.